Metal Mining - Report of Committee on Metal Mine Ventilation. Presented by D. Harrington (with Discussion) (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1927)
The ventilation of metal mines is becoming more of a fundamental requirement than it was 10 or even 5 years ago. There are many reasons for this, and in general they are based on economy or efficiency rather than health or safety, yet the latter enters into the picture in at least some instances. One Montana metal mine which had installed mine fans and a general ventilating system shut down the fan when there was a period of cessation of work; within a few weeks it was found that the underground timbers were becoming so covered with fungus that the fans were put into operation and thereafter continued in operation whether the mine was worked or not. The fungus soon disappeared and the cost of operating the fans was held to be far less than would be the numerous losses from timber decay which quickly started when cessation of air flow was encountered. A large iron ore mine in Michigan had much difficulty in holding men in a slicing region due to foul air under certain surface conditions as to direction of wind. Upon the placing of a moderate sized fan on the surface with some doors, stoppings and regulators underground, not only was the bad air condition removed but there was found to be a decided increase of tonnage per man per shift and timber decay was retarded to a very considerable extent. This particular mining company was rather inclined to be angry when I called attention to some of the what I considered very bad working conditions underground, and the mine superintendent for about a year and a half was on anything but friendly terms with me. Later on when the effect of the placing of the fan was found (the fan had been placed over his protest), that, man came through very nicely with a letter and congratulated me on the recommendation made and congratulated himself and the company on the conditions obtained after the installation of the fan. Poisonous Fumes after Blasting A copper mine in the Southwest with an ore of a high sulfide content has much difficulty due to poisonous fumes after blasting, and the, fan installation is as elaborate as those of many of the most nearly up-to-date coal mines, and coal mine splitting and regulating practices are being